Novel ssDNA Viruses Detected in the Virome of Bleached, Habitat-Forming Kelp Ecklonia radiata - Beattie, Douglas T.; Lachnit, Tim; Dinsdale, Elizabeth A.; Thomas, Torsten; Steinberg, Peter D. (Frontiers in Marine Science, 2018)
Kelp forests provide essential habitats for organisms in temperate rocky shores. Loss of kelp forests has occurred over large areas in a number of temperate regions, including in Australia, where the dominant kelp Ecklonia radiata has been lost from substantial areas of the shoreline. Loss of E. radiata has been associated with environmental stressors, including increased temperature and anthropogenic contaminants, as well as biological factors, such as herbivory. Disease may also play a role, but there is little information on the role of disease in the loss of kelp from coastal ecosystems or on the potential role of pathogenic microorganisms, such as viruses. E. radiata across much of its distribution in Australia can develop a “bleached” phenotype, which may be a disease. To investigate whether the phenotype was associated with a potential viral agent, we shotgun sequenced viral particles that were isolated from kelp with normal (healthy) and bleached phenotypes. Each virome consisted of 380,000 reads, of which 25% were similar to known viruses. All samples were dominated by bacteriophages, but novel ssDNA virus sequences were detected that were almost exclusively in viromes from the bleached kelp phenotype. These ssDNA viruses are covered by 11 contigs that contained complete capsids and characteristic rep genes that were 30–60% similar to those of circular, Rep-encoding ssDNA viruses (CRESS-DNA viruses). CRESS-DNA viruses have not previously been described from macroalgae, and the rep genes were similar to CRESS-DNA viruses from marine water samples, snails, crabs, anemones, but also dragonflies. This raises the interesting possibility that the kelp could be a vector of the CRESS-DNA viruses to other organisms that are associated with the bleached state.